KOORDINASI PENGENDALIAN PENERBANGAN ANTARA KANTOR KEMENTERIAN PERHUBUNGAN DAN KANTOR OTORITAS BANDAR UDARA WILAYAH VI MENGENAI PENGENDALIAN KELAIKUDARAAN - Syahrul, Annilka (Universitas Ekasakti, 2020)
Problems faced in implementing the coordination of Airworthiness control between the Head Office of the Directorate of Airworthiness and Aircraft Operations and the Airport Authority Office. It can be seen from the Directorate of Airworthiness and Aircraft Operations that until now it is still carrying out control activity tasks such as giving directions, technical guidance, licensing extension. The authority to sign the extension of permits (permits, standard airworthiness certificates, and aircraft personnel licenses) granted by the Director General of Civil Aviation to the Head of the Airport Authority Office. The approach used in this research is a normative juridical approach. Based on the results of research and discussion, it can be concluded that: First, the coordination of flight control between the Office of the Ministry of Transportation, Directorate of Airworthiness and Aircraft Operation and the Regional VI Airport Authority Office regarding Airworthiness Control is regulated in the Regulation of the Director General of Air Transportation Number: KP. 459 of 2015 that the Head Office and the Airport Authority Office are carried out harmoniously and tiered according to their respective authorities through the national aviation safety and security database system. However, the implementation of the division of authority for airworthiness control has not been carried out in accordance with the provisions, because the database system referred to in Article 6 of the Regulation of the Director General of Civil Aviation Number: KP. 459 of 2015, not yet available. Second. 2. Constraints found in the flight control coordination arrangements between the Office of the Ministry of Transportation and the Regional VI Airport Authority Office regarding Airworthiness Control are external obstacles and internal constraints. External constraints, namely: 1) the implementation of the control function in the Airworthiness sector in the form of an extension of the aircraft personnel license and the extension of the Advanced Airworthiness certificate (Certificate of Continous Airworthines) in its working area is still being carried out by the Airworthiness Inspector Office of the Ministry of Transportation, Directorate of Airworthiness and Aircraft Operations. Air; 2) the exercise of controlling authority in the signing of an extension of the Aircraft Airworthiness Certificate has not been implemented properly; 3) the authority to carry out functions has not been able to be carried out properly; 4) the arrangement for the placement of Airworthiness inspectors at the Regional VI - Padang Airport Authority Office is not in accordance with the number and qualifications.